Chess classes and executive function skills in 5–6 years old children: evidence from cross-sectional study - Yakushina, Anastasia; Chichinina, Elena; Dolgikh, Aleksandra (Frontiers in Psychology, 2025)
The aim of this study was to compare executive function skills in preschool children who were engaged in chess classes with those who were not. The participants were 88 typically developing 5–6-year-old children. There were two groups with 30 boys and 14 girls in each group: a group of chess players and a group of non-chess players. The results indicated that children who participated in chess classes exhibited significantly higher visuospatial working memory scores compared to their non-chess playing counterparts (U = 731, p = 0.05). Moreover, the analysis revealed no significant differences in the characteristics of extracurricular activities undertaken by the two groups. Consequently, the enhanced visuospatial working memory levels observed in the chess-playing group may be due to their participation in chess classes. Taken together, these findings suggest that chess classes may represent a viable method for enhancing visuospatial working memory in preschool-aged children.